A multiple case study to understand how students experience science and engineering practices - Schaben, Chris; Andersson, Justin; Cutucache, Christine (Frontiers in Education, 2022)
Recent shifts in science curriculum aim to produce students who learn science through the practices of scientists and engineers. Students have varied experiences learning science and engineering practices, including exposure from parents, family, media, and science fairs. We provide evidence that students learn different aspects of science and engineering practices both during in school and out-of-school learning. Several transcending themes emerged from our data. Specific science and engineering practices might be better leveraged to introduce students to scientific research, students saw themselves as scientists, the relevancy of the work drove student learning, and resiliency was important during many of their learning experiences.